Endocrine Mucin-Producing Sweat Gland Carcinoma, a Histological Challenge - Mary Anne Brett; Samih Salama; Gabriella Gohla; Salem Alowami (Hindawi Limited, 2017)
Endocrine mucin-producing sweat gland carcinoma (EMPSGC) is a rare adnexal tumor of the skin with low-grade cytological features and neuroendocrine differentiation. It has a predilection for the skin of the eyelid, but has also been reported in the face and rarely extra-facial locations. The tumor is seen more frequently in women and on average affects the elderly. It is histologically and immunohistochemically analogous to solid papillary carcinoma of the breast/endocrine ductal carcinoma in situ with a nodular, solid, papillary, and/or cribriforming architecture, neuroendocrine differentiation, and mucin production. Since it was first described by Flieder et al. in 1997, less than 60 cases have been reported in literature. We describe the morphological and immunohistochemical features of another case with a review of the common histological differential diagnoses and emphasize the salient features that help distinguish this rare neoplasm.